2015
DOI: 10.1073/pnas.1419051112
|View full text |Cite
|
Sign up to set email alerts
|

Giant reversible, facet-dependent, structural changes in a correlated-electron insulator induced by ionic liquid gating

Abstract: The use of electric fields to alter the conductivity of correlated electron oxides is a powerful tool to probe their fundamental nature as well as for the possibility of developing novel electronic devices. Vanadium dioxide (VO 2 ) is an archetypical correlated electron system that displays a temperature-controlled insulating to metal phase transition near room temperature. Recently, ionic liquid gating, which allows for very high electric fields, has been shown to induce a metallic state to low temperatures i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
108
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 26 publications
14
108
0
Order By: Relevance
“…Our study shows that the VO 2 insulating monoclinic phase becomes metallic at a gate voltage of 2.6 V retaining the monoclinic symmetry. Further, our data suggest that the mechanism of metalization is likely due to oxygen vacancy formation as shown by Jeong et al 18,19 .…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Our study shows that the VO 2 insulating monoclinic phase becomes metallic at a gate voltage of 2.6 V retaining the monoclinic symmetry. Further, our data suggest that the mechanism of metalization is likely due to oxygen vacancy formation as shown by Jeong et al 18,19 .…”
supporting
confidence: 77%
“…This type of switching process requires high electric field, which cannot be achieved by present day dielectric gates and hence calls for electrolytic top gating 14-16 as has been done using ionic liquid (IL) by two groups of Iwasa et al 8,17 and Jeong et al 18,19 . Both the groups showed that above a certain positive gate voltage, the MIT temperature is suppressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Recently, we have shown that not only is the gateinduced metallization dependent on the crystal orientation of epitaxially grown single-crystalline VO 2 films, but that the metallization is accompanied by a significant expansion of the VO 2 lattice. [13] Moreover, both these effects are non-volatile. [13] Adv.…”
mentioning
confidence: 99%
“…Here we investigate an alternative method for controlling the electronic properties via ionic liquid gating. Previous work on VO 2 thin films has shown that liquid electrolyte gating produces structural modifications and leads to the suppression of the metal-insulator transition (11,12). Recent gating experiments on epitaxial WO 3 thin films indicate changes in the out-of-plane lattice parameter, concomitant with the metallization throughout the film volume (13).…”
mentioning
confidence: 99%